Effectiveness of Player Unknown Battleground (PUBG) Video Game in Improving Vocabulary - Sastradwija Putra Perkasa; Dedi Rahman Nur (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
One of the online-based games that are popular right now is PUBG. This online-based game is good to be used as an alternative for the student to learn vocabulary. This study aims to compare whether to learn English vocabulary through PUBG online game than pre adopted course. This paper utilized a pre-test and post-test questionnaire to gather the data. There are observations and reactions to digital games. This study indicated that after playing PUBG the students' mean score is significantly higher than before playing the game, showing the beneficial effect of using video games to improve students' English vocabulary. Video games have basic representations of perception that are interactive. Therefore, from an optimistic viewpoint, integrating video games into the learning process must be viewed. It is not a simple task to create video games packed with instructional features, but it is a standard solution to better understand their assignments. Via problem-solving, decision-making, conclusion-making and collaborative study with their peers, students learn cognitive and beneficial components in addition to fun. Not only do students know about the subject, but they also develop their personalities.